Особливості проектування коаксіальних лінійних двигунів з постійними магнітами - Юр'єва, Олена Юріївна (НТУ "ХПІ", 2017)
Подано принципи проектування коаксіальних лінійних двигунів з постійними магнітами. Наведено принципи обирання електромагнітних навантажень та розмірів постійних магнітів. Представлено формулу машинної постійної для коаксіальних лінійних двигунів. Визначено математичний зв’язок між розмірами постійного магніту, його характеристиками та електромагнітними навантаженнями. Наведені співвідношення між елементами активної частини двигуна. На прикладі двигуна потужністю 500 Вт апробовано запропоновану методику проектування коаксіальних лінійних двигунів з постійними магнітами.

Purpose. Presentation of the principles and the results of design of coaxial linear motor with permanent magnets. Methodology. Suggested design principles are based on the use of Arnold machinery constant. Electric and magnetic loading is determined motor apparent power of motor. Characteristics and dimensions of permanent magnet is determined motor apparent power of motor also. The correctness of the obtained size of the active part of the motor checked draft force. Results. The test calculations are conducted on a 500 W coaxial linear motor for submersible pump plunger. Proposed design principles obtained mathematical relationship between nominal data, electromagnetic characteristics, geometrical dimensions allow creating new and improve existing coaxial linear motors. Originality. Proposed design principles obtained mathematical relationship between nominal data, electromagnetic characteristics, geometrical dimensions allow creating new and improve existing coaxial linear motors. Practical value. These design features proposed for use in research and engineering practice.
Design features of coaxial linear motor with permanent magnets
Keywords: статор; бігун; тягове зусилля; ковзний вузол; електромагнітні навантаження; coaxial linear motor; permanent magnet; design; stator; runner; draft force